Issues in the practice of classroom-based assessment (CBA) in Malay language speaking skills - Shaari, Muhammad Nurfikri; Jamil, Halimah (Human Resource Management Academic Research Society, 2024)
Classroom-Based Assessment (CBA) was first implemented for pupils in 2017. CBA is a set of tests to see and track the extent to which pupils' achievements can be examined, especially in listening and speaking skills for Malay language subject. This study's methodology involved library research, specifically books, articles, and journals. In the implementation of assessment, various matters should be examined by the teachers to ensure that the weaknesses of the pupils and teachers teaching practice can be improved. For this reason, this concept paper investigates two main issues in the practice of CBA in Malay language speaking skills among teachers, which are lacks proficiency in conducting CBA and difficulty in determining pupils’ assessment scoring. The results have significant ramifications that offer essential insights into teachers' assessment processes and expertise, as well as ways to enhance the use of CBA speaking abilities. In addition, this article suggests that to address the concerns identified, teachers' need an assessment training that should be increased. The authorities need to take drastic action to ensure that teachers receive exposure through regular training or workshops so that they truly understand and are knowledgeable in implementing CBA effectively especially in Malay language speaking skills assessment.